Intrinsic anticarcinogenic effects of Piper sarmentosum ethanolic extract on a human hepatoma cell line - Senafi Sahidan; Safian Muhd Fauzi; Zainal Ariffin Zaidah; Wan Omar Wan Haifa Haryani; Zainal Ariffin Shahrul Hisham; Megat Abdul Wahab Rohaya (Cancer Cell International, 2009)
Abstract Background Piper sarmentosum, locally known as kaduk is belonging to the family of Piperaceae. It is our interest to evaluate their effect on human hepatoma cell line (HepG2) for the potential of anticarcinogenic activity. Results The anticarcinogenic activity of an ethanolic extract from Piper sarmentosum in HepG2 and non-malignant Chang's liver cell lines has been previously determined using (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl-tetrazolium bromide) (MTT) assays, where the IC50 value was used as a parameter for cytotoxicity. The ethanolic extract that showed anticarcinogenic properties in HepG2 cells had an IC50 of 12.5 μg mL-1, while IC50 values in the non-malignant Chang's liver cell line were greater than 30 μg mL-1. Apoptotic morphological changes in HepG2 cells were observed using an inverted microscope and showed chromatin condensation, cell shrinkage and apoptotic bodies following May-Grunwald-Giemsa's staining. The percentage of apoptotic cells in the overall population (apoptotic index) showed a continuously significant increase (p < 0.05) in 12.5 μg mL-1 ethanolic extract-treated cells at 24, 48 and 72 hours compared to controls (untreated cells). Following acridine orange and ethidium bromide staining, treatment with 10, 12 and 14 μg mL-1 of ethanolic extracts caused typical apoptotic morphological changes in HepG2 cells. Molecular analysis of DNA fragmentation was used to examine intrinsic apoptosis induced by the ethanolic extracts. These results showed a typical intrinsic apoptotic characterisation, which included fragmentation of nuclear DNA in ethanolic extract-treated HepG2 cells. However, the non-malignant Chang's liver cell line produced no DNA fragmentation. In addition, the DNA genome was similarly intact for both the untreated non-malignant Chang's liver and HepG2 cell lines. Conclusion Therefore, our results suggest that the ethanolic extract from P. sarmentosum induced anticarcinogenic activity through an intrinsic apoptosis pathway in HepG2 cells in vitro.